2020
DOI: 10.1212/wnl.0000000000010418
|View full text |Cite
|
Sign up to set email alerts
|

Location-specific risk factors for intracerebral hemorrhage

Abstract: Objective:To conduct a systematic review and meta-analysis of studies reporting on risk factors according to the location of the intracerebral hemorrhage.Methods:We searched PubMed and Embase for cohort and case-control studies reporting on ≥100 patients with spontaneous intracerebral hemorrhage, that specified the location of the hematoma and reported associations with risk factors published until June 27th 2019. Two authors independently extracted data on risk factors. Estimates were pooled with the generic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 47 publications
4
37
0
2
Order By: Relevance
“…Jolink et al also confirmed that hypertension was associated with the high risk of ICH. Male gender was more likely to be attacked by ICH which might be due to excessive drinking [ 37 ]. A systematic review and meta-analysis of intracerebral hemorrhage have indicated that the incidence of ICH increased with age, especially in patients above 45 years of age, and the incidence rate of males is higher than that of the female patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jolink et al also confirmed that hypertension was associated with the high risk of ICH. Male gender was more likely to be attacked by ICH which might be due to excessive drinking [ 37 ]. A systematic review and meta-analysis of intracerebral hemorrhage have indicated that the incidence of ICH increased with age, especially in patients above 45 years of age, and the incidence rate of males is higher than that of the female patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lobar intracerebral haemorrhage is often caused by cerebral amyloid angiopathy, but hypertension is also an important risk factor. 64 Recent studies reported no statistically significant association between air pollution and haemor rhagic stroke overall. [18][19][20] This finding might suggest that air pollutants exclusively increase intracerebral haemor rhage risk and not subarachnoid haemorrhage.…”
Section: Short-term Exposure To Air Pollution and Risk Of Haemorrhagic Strokementioning
confidence: 98%
“…Impaired vasoregulation due to acute hyperglycemia may enhance perihematomal hypoperfusion in ICH patients, so favouring the development of secondary satellite ischemia brain lesions adding to hemorrhagic damage 48 , 49 . As diabetes mellitus is a specific risk factor for non-lobar ICH 50 , non-diabetic patients with non-lobar ICH might have a higher likelihood of chronical exposure to some degree of unrecognized dysglycemia. Therefore, these patients might also be less vulnerable to the adverse effects of sudden glycemic drops in ischemic perihematomal areas as a consequence of having acquired a higher tolerance to dysglycemia 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Finnish study dichotomized hematoma location as infratentorial versus supratentorial, but supratentorial hemorrhages are not at all homogeneous. Lobar ICH is more often associated with amyloid angiopathy whereas non-lobar ICH is more related to diabetes and hypertensive vasculopathy 33 , 50 , 54 . Moreover, although lobar ICH is characterized by a larger admission hematoma volume and worse neurological impairment, its prognosis is usually better than that of non-lobar ICH 33 , 54 .…”
Section: Discussionmentioning
confidence: 99%